High-capacity ferroferric oxide electrode and preparation method and application thereof

The Fe3O4@CC material was synthesized by hydrothermal method and electrochemical conversion method, and the problem of low specific capacity of the existing negative electrode material was solved, and a high specific capacitance and good cycle life of ferrooxide electrode was achieved.

CN119650319AActive Publication Date: 2025-03-18JILIN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411775585.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-18
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The specific capacity of existing negative electrode materials is relatively low, limiting the energy density and overall performance of the supercapacitor.

Method used

Fe3O4@CC material was synthesized by hydrothermal method and electrochemical conversion method, and oxygen functional groups on the surface of the carbon cloth substrate were used as the nucleation site of iron oxide nanoparticles to achieve uniformity of particle size and high specific capacity.

Benefits of technology

The preparation of a high-capacity ferrooxide electrode is achieved, achieving a specific capacitance of about 1000 F/g, and has good cycle life and charge transfer capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650319A_ABST
    Figure CN119650319A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of electrode materials, and provides a preparation method of a high-capacity ferroferric oxide electrode, which comprises the following steps: putting an iron source salt solution and a carbon cloth substrate into a reaction kettle together, then putting the reaction kettle into a drying oven for hydrothermal reaction, obtaining a Fe2O3 coated CC precursor after the hydrothermal reaction is finished, and cleaning and drying the Fe2O3 coated CC precursor; taking the Fe2O3-coated CC precursor as a working electrode, taking a platinum sheet and a calomel electrode as a counter electrode and a reference electrode respectively, taking a potassium hydroxide solution as an electrolyte, carrying out an electrochemical oxidation reduction process on the working electrode by using a cyclic voltammetry method or a constant-current charge-discharge method until the Fe2O3-coated CC precursor is completely converted into a Fe3O4-coated CC active substance, taking out the Fe2O3-coated CC active substance, and cleaning and drying the Fe2O3-coated CC active substance to obtain the Fe2O3-coated CC composite material. The high-capacity ferroferric oxide electrode can be obtained. The invention also provides a high-capacity ferroferric oxide electrode and application thereof. The Fe3O4-coated CC material is synthesized through a hydrothermal method and an electrochemical conversion method, and the ultrahigh specific capacitance close to the theoretical capacity is achieved and reaches about 1000 F / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a high-capacity ferroferric oxide electrode and a preparation method and application thereof. Background Art

[0002] With the decreasing reserves of traditional energy and the serious environmental pollution caused by its combustion products, the development and utilization of clean energy is urgent. Supercapacitors and batteries are two typical electrochemical energy storage devices, which have the advantages of high power density, good cycle stability, and low maintenance cost. However, the lower energy density limits the further development of supercapacitors. The capacity of supercapacitor positive electrode materials has mostly reached 1000-2000F / g, while the negative electrode material is only 100-500F / g. If the energy density of energy storage devices is to be improved, the specific capacity of the negative electrode material must be improved first.

[0003] Currently, commercial negative electrode materials are mainly multifunctional carbon materials, but their specific capacity is low (about 150F / g), which greatly reduces the overall performance of energy storage devices and limits their application. Traditional iron-based oxide (iron oxide, iron oxyhydroxide) negative electrodes rely on Faraday reactions to significantly improve the specific capacity (about 300F / g), but there is still a large gap with the theoretical capacity (1060F / g). Most of the existing technologies use hydrothermal / solvent thermal methods, electrodeposition methods, electrochemical oxidation methods, molten salt methods, electrospinning methods, etc. to prepare negative electrode materials. Among them, it is not easy to control the particle size and loading amount during the hydrothermal / solvent thermal synthesis process, and it is easily affected by temperature and concentration to obtain particles of uneven size, and it is also affected by factors such as salt solution and substrate to obtain metal oxide materials with different morphologies; the electrodeposition method deposits metal hydroxides (hydroxy oxides) on the substrate with the help of high-potential Faraday reaction. Due to the hydrophilicity and hydrophobicity of the substrate to the solution, the active material is deposited unevenly, and too large or too small a deposition current can affect its morphology and deposition loading amount; the electrochemical oxidation method electrochemically converts the precursor sample into the target active material through cyclic voltammetry or constant current charge and discharge method, but different activation methods lead to active material samples with different crystal phases or morphologies; the molten salt method may cause the concentration of active materials on the inner surface to decrease due to the movement of active materials to the outer surface, resulting in uneven distribution of active components on the carrier; the active materials synthesized by electrospinning often have the characteristics of large size and low structural strength, which cannot enable the active materials to fully participate in the energy storage reaction. Summary of the invention

[0004] The purpose of the embodiments of the present invention is to provide a method for preparing a high-capacity ferroferric oxide electrode, aiming to solve the problems raised in the above-mentioned background technology.

[0005] The embodiment of the present invention is implemented as follows: a method for preparing a high-capacity ferroferric oxide electrode comprises the following steps:

[0006] (1) placing an iron source salt solution and a carbon cloth substrate into a reaction kettle, and then placing the reaction kettle in an oven for hydrothermal reaction. After the hydrothermal reaction is completed, a Fe2O3@CC precursor is obtained, which is then cleaned and dried.

[0007] (2) The Fe2O3@CC precursor is used as the working electrode, the platinum sheet and the calomel electrode are used as the counter electrode and the reference electrode respectively, and the potassium hydroxide solution is used as the electrolyte. The working electrode is subjected to an electrochemical oxidation-reduction process by cyclic voltammetry or constant current charge-discharge method until the Fe2O3@CC precursor is completely converted into the Fe3O4@CC active substance. After taking it out, it is cleaned and dried to obtain a high-capacity ferroferric oxide electrode.

[0008] Preferably, in step (1), the method for preparing the iron source salt solution comprises the following steps: mixing 3 mmol of Fe(NO3)3 or FeCl3 with 40 mL of deionized water and stirring evenly to obtain a clear solution.

[0009] Preferably, in step (1), the temperature of the hydrothermal reaction is 120° C. and the time is 24 h.

[0010] Preferably, in step (2), the parameters of the cyclic voltammetry are 2 mV / s scan rate, 10 cycles or 4 mV / s, 20 cycles or 8 mV / s, 50 cycles or 20 mV / s, 100 cycles, and the potential window is -1.2-0 V.

[0011] Preferably, in step (2), the parameter of the constant current charge-discharge method is a current density of 30 A / g.

[0012] Preferably, in step (1) and step (2), the cleaning and drying are specifically: cleaning with deionized water and then drying in an oven at 60°C.

[0013] Another object of an embodiment of the present invention is to provide a high-capacity ferrosoferric oxide electrode, which is prepared by the above-mentioned preparation method.

[0014] Another object of the embodiment of the present invention is to provide an application of a high-capacity ferroferric oxide electrode in the preparation of a supercapacitor.

[0015] The embodiment of the present invention provides a method for preparing a high-capacity ferroferric oxide electrode. The Fe3O4@CC material is synthesized by a hydrothermal method and an electrochemical conversion method. The oxygen functional groups on the surface of the carbon cloth substrate are used as the nucleation sites of iron oxide nanoparticles. The grains grow uniformly at a relatively low temperature (120°C) and do not agglomerate, which greatly improves the uniformity of the particle size. During the electrochemical activation process, a reduction reaction occurs at about -1.1V to partially reduce the +3-valent Fe to +2-valent Fe, and then an oxidation reaction occurs at about -0.7V to lose some electrons. After multiple activations, a relatively stable electrochemical state is reached, and the crystal phase is converted, that is, the iron oxide is converted into ferroferric oxide. In the subsequent charge and discharge process, the Fe3O4@CC negative electrode achieves an ultra-high specific capacitance close to the theoretical capacity, reaching about 1000F / g, due to its unique inverse spinel structure and the characteristics of the multivalent state of iron atoms that are easy to gain or lose electrons, as well as sufficient Faraday reaction brought about by the particle size. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD spectrum and SEM morphology of the Fe2O3@CC precursor provided in the embodiment of the present invention;

[0017] Figure 2 XRD spectrum and SEM morphology of the Fe3O4@CC active material provided in the embodiment of the present invention;

[0018] Figure 3 A cyclic voltammetry curve of electrochemical conversion of the Fe2O3@CC precursor provided in an embodiment of the present invention by cyclic voltammetry;

[0019] Figure 4 The charge-discharge curve of the Fe2O3@CC precursor provided in the embodiment of the present invention when the charge-discharge test is performed directly without electrochemical activation;

[0020] Figure 5 The XRD spectrum and SEM morphology of the mixture FeOOH+Fe3O4@CC provided in the embodiment of the present invention;

[0021] Figure 6 The cyclic voltammetry curve of the Fe3O4@CC active material provided in the embodiment of the present invention;

[0022] Figure 7 The constant current charge and discharge curve of the Fe3O4@CC active material provided in the embodiment of the present invention;

[0023] Figure 8 The EIS spectrum of the Fe3O4@CC active material provided in the embodiment of the present invention;

[0024] Fig. 9The cyclic voltammetry curve of the mixture FeOOH+Fe3O4@CC provided in the embodiment of the present invention;

[0025] Fig.10 The constant current charge-discharge curve of the mixture FeOOH+Fe3O4@CC provided in the embodiment of the present invention;

[0026] Fig.11 The rate performance of the mixture FeOOH+Fe3O4@CC provided in the embodiment of the present invention;

[0027] Fig.12 The chemical performance comparison results of Fe3O4@CC active material, RuO2·xH2O and AC provided in the embodiments of the present invention;

[0028] Fig.13 The specific capacitance and working potential window of the Fe3O4@CC active material provided in the embodiment of the present invention are applied in different types of aqueous electrolytes. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0030] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0031] Embodiment 1: A high-capacity ferroferric oxide electrode, the preparation method of which comprises the following steps:

[0032] (1) Mix 3 mmol of Fe(NO3)3 with 40 mL of deionized water and stir to obtain a clear solution. Cut a commercial carbon cloth CC of appropriate size (2 cm*3 cm) (the carbon cloth is not limited to brands, and can be Carbon Energy carbon cloth, Hesen carbon cloth, Toray carbon cloth, etc.; hydrophilic carbon cloth can be used directly, or the raw carbon cloth can be pretreated with concentrated acid, plasma etched, high-temperature annealed, etc. to increase the number of surface oxygen functional groups). Put the solution and carbon cloth into a 50 mL reactor and keep it in a 120 ° C oven for 24 h. After natural cooling, take out the carbon cloth sample loaded with iron oxide, wash it with deionized water and dry it in a 60 ° C oven. It is recorded as Fe2O3@CC precursor;

[0033] (2) The Fe2O3@CC precursor sample was cut into a suitable size (1 cm*1.5 cm), and an aqueous alkaline three-electrode electrochemical system was prepared. The Fe2O3@CC precursor was used as the working electrode, the platinum sheet was used as the counter electrode, the calomel electrode was used as the reference electrode, and the 2M potassium hydroxide solution was used as the electrolyte. Cyclic voltammetry was used as the activation method. The scan rate was set to 2 mV / s, the number of cycles was 10, and the potential window was -1.2-0 V. The Fe2O3@CC precursor was completely electrochemically converted until no obvious redox peaks appeared. The electrode sheet was taken out, cleaned with deionized water, and dried in an oven at 60°C. It was recorded as the Fe3O4@CC active material.

[0034] Performance Test:

[0035] The Fe2O3@CC precursor synthesized in Example 1 was analyzed by XRD diffractometer and scanning electron microscope, and the XRD spectrum and SEM morphology were obtained as shown in the figure. Figure 1 As shown, according to Figure 1 It can be seen that the Fe2O3@CC precursor is an α-Fe2O3 crystal phase, and its particle size is uniform, about 40 nm;

[0036] The Fe3O4@CC active material prepared in Example 1 was analyzed by XRD diffractometer and scanning electron microscope, and the XRD spectrum and SEM morphology were obtained as shown in the figure: Figure 2 As shown, according to Figure 2 It can be seen that the Fe3O4@CC active material is a cubic inverse spinel structure, and its particle size has not changed much compared with that before transformation;

[0037] The cyclic voltammetry curve of the electrochemical conversion of Fe2O3@CC precursor is shown in Figure 3 As shown, it is the process of electrochemical conversion of α-Fe2O3 crystal phase into Fe3O4;

[0038] The Fe2O3@CC precursor synthesized in Example 1 was directly subjected to charge and discharge test (current density was 2 A / g) without electrochemical activation, and the charge and discharge curves were as follows: Figure 4 As shown, according to Figure 4 It can be seen that there is an obvious charge-discharge platform. In this platform stage, part of the precursor iron oxide is converted into iron oxyhydroxide, and the other part is converted into iron tetroxide. This reaction is irreversible and is a side reaction in the charge-discharge process. After about 10 cycles of charge and discharge, the side reaction ends. Among them, iron oxyhydroxide provides almost no pseudocapacitance, which greatly reduces the capacitance of the electrode material.

[0039] The mixture FeOOH+Fe3O4@CC generated during the charge and discharge test was analyzed, and the XRD spectrum and SEM morphology were obtained as shown in Figure 5As shown, it is obvious that two crystal phases coexist, among which Fe3O4 is a cubic inverse spinel structure, while FeOOH is a hexagonal crystal. The particles have changed greatly compared with those before the transformation. The original particle morphology is difficult to distinguish, and more are irregular nanosheets and nanorods.

[0040] The electrochemical performance of the Fe3O4@CC active material prepared in Example 1 was tested, and the cyclic voltammetry curves (at different scan rates) were obtained as follows: Figure 6 As shown, the constant current charge and discharge curve (different current density) is as follows Figure 7 As shown, the EIS spectrum is as follows Figure 8 As shown, it can be calculated that the Fe3O4@CC active material exhibits a specific capacity of up to 1230F / g at a current density of 1A / g, and has a very small mass transfer internal resistance, which also reflects its efficient and rapid charge transfer ability;

[0041] The electrochemical performance of the mixture FeOOH+Fe3O4@CC was tested, and the cyclic voltammetry curves (different scan rates) were obtained as follows: Fig. 9 As shown, the constant current charge and discharge curve (different current density) is as follows Fig.10 As shown, the rate performance is Fig.11 As shown, it can be calculated that the mixture FeOOH+Fe3O4@CC exhibits a specific capacity of up to 776F / g at a current density of 1A / g, which is much lower than the Fe3O4@CC active material after activation by electrochemical oxidation;

[0042] The performance of the Fe3O4@CC active material prepared in Example 1 and typical supercapacitor electrode materials RuO2·xH2O and AC were tested, and the results were as follows: Fig.12 As shown, AC activated carbon only exhibits a specific capacitance of about 150F / g, but its cycle life is excellent, and it can still retain 98.6% of the original capacity after 10,000 charge and discharge cycles; RuO2·xH2O only exhibits a specific capacitance of about 600F / g, and decays rapidly, and only retains 61.1% of the original capacity after 10,000 charge and discharge cycles; and the Fe3O4@CC active material prepared in the embodiment of the present invention not only exhibits a specific capacitance of up to about 1200F / g, but also has an excellent cycle life, and can still retain 97.4% of the original capacity after 10,000 charge and discharge cycles;

[0043] The Fe3O4@CC active material prepared in Example 1 was applied to different types of aqueous electrolytes, and its specific capacitance and working potential window were as follows: Fig.13 As shown, it can be seen that the Fe3O4@CC active material of the embodiment of the present invention can be used in alkaline, neutral and acidic electrolyte systems, and can well adapt to multivalent metal ions such as Mg 2+ 、Al3+ In addition, it still has good capacitance performance in redox electrolyte.

[0044] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-capacity ferroferric oxide electrode, characterized in that: The following steps are involved: (1) placing an iron source salt solution and a carbon cloth substrate into a reaction kettle, and then placing the reaction kettle in an oven for hydrothermal reaction. After the hydrothermal reaction is completed, a Fe2O3@CC precursor is obtained, which is then cleaned and dried. (2) The Fe2O3@CC precursor is used as the working electrode, the platinum sheet and the calomel electrode are used as the counter electrode and the reference electrode respectively, and the potassium hydroxide solution is used as the electrolyte. The working electrode is subjected to an electrochemical redox process by cyclic voltammetry or constant current charge-discharge method until the Fe2O3@CC precursor is completely converted into the Fe3O4@CC active substance. After taking it out, it is cleaned and dried to obtain a high-capacity ferroferric oxide electrode.

2. The method for preparing a high-capacity ferroferric oxide electrode according to claim 1, characterized in that: In step (1), the method for preparing the iron source salt solution comprises the following steps: mixing 3 mmol of Fe(NO3)3 or FeCl3 with 40 mL of deionized water and stirring evenly to obtain a clear solution.

3. The method for preparing a high-capacity ferroferric oxide electrode according to claim 1, characterized in that: In step (1), the temperature of the hydrothermal reaction is 120° C. and the time is 24 hours.

4. The method for preparing a high-capacity ferroferric oxide electrode according to claim 1, characterized in that: In step (2), the parameters of the cyclic voltammetry are 2 mV / s scan rate, 10 cycles or 4 mV / s, 20 cycles or 8 mV / s, 50 cycles or 20 mV / s, 100 cycles, and the potential window is -1.2-0 V.

5. The method for preparing a high-capacity ferroferric oxide electrode according to claim 1, characterized in that: In step (2), the parameter of the constant current charge-discharge method is a current density of 30 A / g.

6. The method for preparing a high-capacity ferroferric oxide electrode according to claim 1, characterized in that: In step (1) and step (2), the cleaning and drying are specifically: cleaning with deionized water and then drying in an oven at 60°C.

7. A high-capacity ferroferric oxide electrode, characterized in that: The preparation method is as described in any one of claims 1 to 6.

8. Use of the high-capacity ferroferric oxide electrode as claimed in claim 7 in preparing a supercapacitor.

Citation Information

Patent Citations

  • Carbon-coated ferroferric oxide and preparation method and application of carbon-coated ferroferric oxide in lithium battery

    CN103117388A

  • A flexible electrode, a preparation method and an application thereof

    CN109065371A